Getting your wires crossed: evidence for fast processing of L1 idioms in an L2 - Carrol, Gareth; Conklin, Kathy (Cambridge University Press, 2014)
Monolingual speakers show priming for idiomatic sequences (e.g. a pain in the neck) relative to matched controls (e.g. a pain in the foot); single word translation equivalents show cross-language activation (e.g. dog–chien) for bilinguals. If the lexicon is heteromorphic (Wray, 2002), larger units may show cross-language priming in the same way as single words. We used the initial words of English idioms (e.g. to spill the . . . beans) and transliterated Chinese idioms (e.g. draw a snake and add . . . feet) as primes for the final words in a lexical decision task with high proficiency Chinese–English bilinguals and English monolinguals. Bilinguals responded to targets significantly faster when they completed a Chinese idiom (e.g. feet) than when they were presented with a matched control word (e.g. hair). The results are discussed in terms of conceptual activation and lexical translation processes, and are also incorporated into a dual route model of formulaic and novel language processing.